Reforming premium amount in the Indonesian National Health Insurance System program using system dynamics. Issue 1 (1st January 2021) - Kurnianingtyas, Diva; Santosa, Budi; Siswanto, Nurhadi
Abstract: The National Health Insurance System (NHIS) is a government program to help the health needs of its population such as in Indonesia (INHIS). However, there are obstacles to implementing it, which is shown by the results of program evaluations every year that there is a deficit problem, starting in 2014 until 2019 to and even expected to increase in the following years. One of the possible deficits is due to inefficient patient behavior and referral system which will affect the premium amount. The goal is to evaluate and plan further policies with efficient premiums amount. System dynamics is used to simulate the effects of ability-to-pay, willingness-to-pay, salary, age, health cost each customer, and fund inventory. The historical data are used from INHIS from 2014 to 2019, then projected until 2030. The simulation results show that the health costs considered for determining the premiums are critical to the financial stability. If the premium is not in accordance with the customer's ability, the government will have to subsidise to avoid deficit. In addition, PPU customers who are already retired will automatically become to BP customers, which will also affect INHIS 'financial condition.